2011
DOI: 10.1140/epjd/e2011-20366-x
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic homogenization of the laser intensity to improve the irradiation uniformity of capsules directly driven by thousands laser beams

Abstract: Abstract. Illumination uniformity of a spherical capsule directly driven by láser beams has been assessed numerically. Láser facilities characterized by ND = 12, 20, 24, 32, 48 and 60 directions of irradiation with associated a single láser beam or a bundle of NB láser beams have been considered. The láser beam intensity profile is assumed super-Gaussian and the calculations take into account beam imperfections as power imbalance and pointing errors. The optimum láser intensity profile, which minimizes the roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…This is a natural way in order to reduce the imperfections associated to the whole bundle. It is found that the illumination uniformity scales as 1/N 1 / 2 tot and is given [16,17] by (N tot ) = [ where N D is the number of irradiation directions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a natural way in order to reduce the imperfections associated to the whole bundle. It is found that the illumination uniformity scales as 1/N 1 / 2 tot and is given [16,17] by (N tot ) = [ where N D is the number of irradiation directions.…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that the optimal focal spot shape depends on the beam imperfections [13] and that taking beam imperfection into account the illumination uniformity is degraded by about one order of magnitude [11]. Finally, it is shown that the use of bundles [14,15] of N B beamlets (laser beam unit) associated to each irradiation direction introduces a stochastic homogenization of the laser intensity which benefits the irradiation uniformity [16,17]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2002; Temporal et al. 2011 a , 2013, 2014 a ; Temporal & Canaud 2011 b ; Tian et al. 2015), but the validity of its solutions has only been partially tested in two-dimensional (Temporal et al.…”
Section: Introductionmentioning
confidence: 99%
“…The model can also include statistical analyses that take into account beam uncertainties such as power-imbalance, pointing error and target positioning. Several studies have been performed to analyze the capsule illumination uniformity for different facilities (Murakami, et al, 1993(Murakami, et al, , 1995(Murakami, et al, , 2010Canaud et al, 2002;Temporal et al, 2009Temporal et al, , 2010aTemporal et al, , 2010bTemporal et al, , 2011aTemporal et al, , 2011bTemporal et al, , 2014aTemporal et al, , 2014b. In these studies it has been assumed that the quality of the illumination (usually measured by a rootmean-square deviation of the incident intensity on a 2/8 spherical surface) is representative of the non-uniformity induced in the first shock wave, also called imprint phase.…”
Section: Introductionmentioning
confidence: 99%